AN ANALYSIS OF STUDENTS' PERCEPTIONS OF PROBLEM-BASED LEARNING MODELS IN ENGLISH LANGUAGE LEARNING - Inayah, Arin; Fariza Alvian Zulkarnain; Nur Hasibin (LUNAR, 2024)
Problem-based learning is one of the innovative learning models that can provide active learning conditions. Problem Based Learning uses individual, group, and environmental intelligence to solve problems with the learning process. The purpose of this study was to analyze students' perceptions of problem-based learning model in English learning. This research used qualitative approach of survey type. The data collection technique used a questionnaire. The data from questionnaire was analyzed by using Likert scale. Sampling technique using quota sample, selected 23 students from XII at MAU Nurul Iman. The data analysis determined based on 7 indicators, 1. Student perceptions in terms of student and teacher interaction are in the agree category with a percentage of 67%, 2. Student perceptions in terms of motivation / increasing student learning interest are in the strongly agree category with a percentage of 82%, 3. Student perceptions of competency in understanding course material are in the agree category with a percentage of 67%, 4. Student perceptions of critical, effective and efficient thinking competencies are in the agree category with a percentage of 65%, 5. Student perceptions of good time management competencies are in the strongly agree category with a percentage of 85%, 6. Student perceptions in terms of good student learning outcomes are in the strongly agree category with a percentage of 85%, 7. Student perceptions of the appropriateness of the application of learning models with subject characteristics are in a agree category with a percentage of 67%. All the percentage show that the categories of students’ perception in problem based learning models in english language learning is in “agree” categories.